2020
DOI: 10.1007/s11051-020-04800-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of iron oxide nanoparticles with different coatings in zebrafish larvae

Abstract: We report on the effect of different coatings (dextran, chitosan, polyethylene glycol, carboxy-silane, and silica) in the toxicity elicited by superparamagnetic iron oxide nanoparticles (SPIONs) in the developing zebrafish (Danio rerio). Animals were exposed to nanoparticle concentrations ranging from 0.125 to 8.0 mM of Fe during the first 5 days after fertilization. Embryotoxicity parameters (survival, hatching rate, and the incidence of anatomical malformations) and behavioral patterns (locomotion during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…Still, Fe content was similar for cells treated with 50 and 100 µg/mL, suggesting a saturation in the internalization capacity of the cells at high NP concentrations. Saturation in Fe uptake has also been found in vivo in zebrafish larvae exposed to similar SPION-DX nanoparticles 39 , but not when U87 cells were treated with iron oxide nanoparticles coated with PEG 40 . Thus, saturation of uptake is not related to the iron oxide itself, but to the coating properties which directly influences the interaction between the cell and the particle 41,42 .…”
Section: Nanoparticle Internalization and Citotoxicitymentioning
confidence: 88%
“…Still, Fe content was similar for cells treated with 50 and 100 µg/mL, suggesting a saturation in the internalization capacity of the cells at high NP concentrations. Saturation in Fe uptake has also been found in vivo in zebrafish larvae exposed to similar SPION-DX nanoparticles 39 , but not when U87 cells were treated with iron oxide nanoparticles coated with PEG 40 . Thus, saturation of uptake is not related to the iron oxide itself, but to the coating properties which directly influences the interaction between the cell and the particle 41,42 .…”
Section: Nanoparticle Internalization and Citotoxicitymentioning
confidence: 88%
“…The toxicity of iron oxide nanoparticles with different coatings (dextran, chitosan, polyethylene glycol, carboxy-silane, and silica) on zebrafish embryos and larvae has also been reported. The results suggest that toxicity, as measured by hatching rate, malformations, behavior, and survival, was not observed for most of the nanocomposites, except those treated with chitosan, where mortality rates were 100% for concentrations higher than 2 mM (millimolar), thus suggesting further investigation of these types of coatings [ 49 ]. Therefore, the zebrafish model is a valid model for evaluating the toxicity of simple or complex nanocomposites such as those evaluated in this study (MNP, MNP+APTES, MNP+APTES+Cys, MNP+Cys, and MNP+CAS).…”
Section: Discussionmentioning
confidence: 99%
“…This is further demonstrated by the fact that proper surface coating of the IO NPs could ameliorate the observed adverse effects to a certain degree underlying again the importance of the physicochemical composition of nanoparticles in the induction of toxicity and teratogenicity [89]. Indeed, it has been shown that specific coatings, such as dextran or polyethylene, can significantly reduce the toxicity of IO NPs for a wide range of concentrations [77,94].…”
Section: Effects Of Io Nps On Zebrafish During Developmentmentioning
confidence: 95%
“…It follows that the response of IO NPs to an external magnetic field (MF) is influenced by their composition, as well as by their dimension [5]. Indeed, the coating does not only prevent the IO NPs from aggregating and protects them from environmental influences but importantly confers the basis for the attachment of other biomolecules creating a plethora of opportunities for possible applications [77]. Notably, IO NPs are so far the only class of metallic nanoparticles that have been approved for clinical use, i.e., in cancer bioimaging, hyperthermia-based therapy, and the treatment of iron deficiency [78].…”
Section: Iron Oxide Nanoparticles (Io Nps)mentioning
confidence: 99%